2018
DOI: 10.5811/cpcem.2018.6.38106
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care Ultrasound Diagnosis of an Atypical Acute Aortic Dissection

Abstract: Aortic dissections have a vast array of clinical presentations that rarely follow traditional teachings. Dissections are rapidly fatal conditions requiring immediate diagnosis and treatment to reduce morbidity and mortality. We present a case of an acute aortic dissection presenting as abrupt onset, atraumatic leg pain with absent distal extremity pulses. The prompt use of point-of-care ultrasound detected an intimal flap within the abdominal aorta allowing immediate surgical consultation and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Diagnosis of aortic dissection can be made by CT, magnetic resonance imaging, and ultrasound. Studies done to ascertain the sensitivity and specificity of ultrasound in the diagnosis of aortic dissection show wide variability from a sensitivity of 52–80% and a specificity from 0–100% 13,15. The presence of an intimal flap, however, was found to be 100% specific and 67% sensitive for aortic dissection 14,15.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of aortic dissection can be made by CT, magnetic resonance imaging, and ultrasound. Studies done to ascertain the sensitivity and specificity of ultrasound in the diagnosis of aortic dissection show wide variability from a sensitivity of 52–80% and a specificity from 0–100% 13,15. The presence of an intimal flap, however, was found to be 100% specific and 67% sensitive for aortic dissection 14,15.…”
Section: Discussionmentioning
confidence: 99%
“…Studies done to ascertain the sensitivity and specificity of ultrasound in the diagnosis of aortic dissection show wide variability from a sensitivity of 52–80% and a specificity from 0–100% 13,15. The presence of an intimal flap, however, was found to be 100% specific and 67% sensitive for aortic dissection 14,15. Although ultrasound should never be the definitive test for aortic dissection, as it lacks sufficient sensitivity, the presence of an intimal flap is highly specific 4.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 While CTA is considered one of the gold standards for diagnosing aortic dissections, point of care ultrasound offers a noninvasive way to begin diagnostic evaluation of a critical patient without leaving the bedside. 7,8 In a study by Wang et al, emergency physicians used POCUS in patients with suspected aortic dissection compared to CTA, which revealed that POCUS had a sensitivity of 86.4% and a specificity of 100.0%. 9,10 While ultrasound is helpful in diagnosing an aortic dissection, a negative bedside ultrasound does not completely exclude aortic pathology.…”
Section: Discussionmentioning
confidence: 99%
“…There are limitations, however, as results are largely operator and patient dependent. However, other imaging studies including CTA of the chest continues to be the gold standard for diagnosing acute dissections 6–8 …”
Section: Discussionmentioning
confidence: 99%
“…However, other imaging studies including CTA of the chest continues to be the gold standard for diagnosing acute dissections. [6][7][8] JACEP Open 2020;1:1763-1764. wileyonlinelibrary.com/journal/emp2 1763…”
Section: F I G U R E 1 Head Ct Reveals Right Hemispheric Infarctionmentioning
confidence: 99%